The significance of constructivist classroom practice in national curricular design. Issue 1 (2nd January 2016) - Booyse, Celia; Chetty, Rajendra
ABSTRACT: Evidence of the value of constructivist theory in the classroom is especially important for educational practice in areas of poverty and social challenge. Research was undertaken in 2010 into the application of constructivist theory on instructional design. The findings of this research are particularly relevant to the current curricular crisis in South Africa which threatens to side-line constructivist priorities and return learners to rote learning from textbooks. The findings are situated here within the national debate over curricular design and instructional models. Placing instructional design within the larger context of national pedagogical contestation provides important evidence of the central role of Freirean imperatives for South Africa's educational future. This article indicates that a constructivist framework, when pertinently arranged, provides holistic and sustainable procedures for knowledge creation. The findings from the research project showed that, in an environment conducive to learning, learners become self-motivated and better able to master the next phase of the curriculum. As a result of the constructivist framing, participants grew into strategic and effective learners who took responsibility for their own learning. These findings add weight to the call for reconsideration of constructivist foundations in national curriculum design.